An Analysis Of Students' Speaking Difficulties at Eighth Grade Smpit At-Taqwa Surabaya - Nur Hidayat; Zhela Meylinda Clarita (IJET (Indonesian Journal of English Teaching), 2020)
The purpose of this study was to investigate the difficulties of students in speaking English. The researcher used a qualitative descriptive method in this study. The subjects of this study were eighth-grade students A and D SMPIT At-Taqwa 2018/2019 academic year consisting of 40 students and English teachers. Data collections of this study were observation, student questionnaires, and student and teacher interviews. The results of this study indicate that 25% of students have difficulty speaking English. The efforts made by students and teachers to overcome difficulties in speaking English such as: taking English tutoring, listening English songs, practicing reading, writing and speaking at home and school. They also communicate through social media with foreign citizens, joining English Camp, watching western movies or change film subtitles with English. Then the solution given by the teacher is an additional lesson hour to support students who felt difficult in speaking English.